Editor’s note - Chen, Yu; Chen, Wenhuan (The Journal of Medicine, Humanity and Media, 2025)
This issue of Journal of Medicine, Humanity and Media (Vol. 3, No. 3) centers on the theme of "Reconstructing the Knowledge System of Health Communication in the Digital Intelligence Era," which is also the core topic of the 8th International Conference on "Medicine, Humanity and Media" (MHM2025) and the Doctoral Forum. This issue presents curated content from the conference, focusing on paradigm shifts and ethical challenges in health communication amid technological advancements. In the current era of rapid digital development, the importance of effectively constructing and applying knowledge systems in health communication has become increasingly evident. How to leverage technological advantages to enhance communication efficacy while addressing the issues brought by technology and ensuring human-centered health communication has become a key concern for researchers.